Mitigasi Risiko Riba pada Transaksi Dompet Digital Syariah: Studi Komparatif Dana Mengendap dan Qard pada Fitur Cashback - Qutlubey Seyyeroh; Zahrotul Maulidia; Maghfirah Maghfirah; Renafilatus Sakinah; Ahmad Budi Susetyo (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
Financial technology growth via digital wallets in Indonesia offers transaction convenience but challenges Sharia compliance. The main issues involve managing floating funds and cashback rewards, which risk exposure to riba. This study aims to examine and compare riba risk mitigation strategies in both areas. Employing normative legal research with qualitative, comparative, and conceptual approaches, it utilizes library research from DSN-MUI Fatwas, the Qur’an, Hadith, and fiqh muamalah literature. The findings reveal that floating fund riba risks can be minimized by depositing assets in Islamic financial institutions using wadiah or mudharabah contracts to avoid riba nasi’ah. Meanwhile, cashback riba risks are prevented by shifting the contract from qard to ju’alah or hibah mu’allaq, treating incentives as transaction rewards rather than loan benefits. Comparative analysis shows floating fund mitigation is structural, while cashback is reconstructive. Both work effectively under Sharia Supervisory Board monitoring. In conclusion, compliance requires practical execution via appropriate contracts, transparent supervision, and public education. Therefore, contract standardization by DSN-MUI and OJK, alongside enhanced Islamic financial literacy, is necessary.